Kinetics of the Enzymatic Hydrolysis of Sweet Cassava Starch and Bitter Cassava Flour and Gadung (Dioscorea hispida Dennst) Flour at Low Temperature - Hargono Hargono; Bakti Jos; Andri Cahyo Kumoro (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Starch is a potential substrate for this purpose, but the extra cost is needed to hydrolyze it into reducing sugar. As an alternative to the expensive and energy demanding conventional hydrolysis process, the low-temperature hydrolysis is being studied. Granular Starch Hydrolysing Enzyme (GSHE) was used in the process to degrade starch into reducing sugar at 30°C and pH 4. The substrates included bitter cassava flour, sweet cassava starch, and gadung flour. Starch concentrations studied were 50, 100, 150, 200, 250, 300, 350, and 400 g/L, respectively, while concentration of enzyme was 1.5 % (w/w). The optimum condition of the process was hydrolysis using 200 g/L of substrate concentration and enzyme  concentration of 1.5% for 12 h. It was found that the reducing sugar was  49.3  g/L and the productivity of reducing sugar (Qrs) was 4.11 (gL-1 h-1).   Lineweaver-Burk plot of Michaelis-Menten equation was used to study the inhibition kinetics. The Michaelis-Menten constants (Km)  for these three substrates were determined as 141.64 g/L, 137,64 g/L and 140.84 g/L for bitter cassava flour, sweet cassava starch, and gadung flour, respectively. The value of  Vm/Km, which denotes the affinity of the enzyme to the substrate, were determined and compared, and the result showed that the affinity (Vm) to the enzyme to this substrate followed  the order of sweet cassava starch˃ bitter cassava flour˃ gadung flour, and all are non-competitive inhibitor, while the  Ki value was 0.022 h -1.